The changing spread dynamics of banana Xanthomonas wilt (BXW) in Uganda - Kubiriba, J.; Bagamba, F.; Rockfeller, E.; Tushemereirwe, W.K. (African Journals Online (AJOL), 2012)
Banana Xanthomonas wilt still remains a serious threat to banana production in Uganda. Although the desired long term control strategy would have been use of resistance, no sources of resistance have been found. Further the transgenic resistance under development will only be deployed in the long run. In the meantime, cultural control, remains the driver of BXW management strategy in Uganda. This requires continuous effort by the farmers and other stakeholders. It is imperative that disease spread information be continuously updated to sustainably control BXW. The study was conducted to update the status of BXWto inform the continuous refinement of the control strategy of BXW control in across all the epidemics zones in Uganda. BXW incidence increased from about 1% between 2005 and 2006 to about 3.8% in 2010 in the threatened areas. The BXW prevalence increased from below 5 to 34.4% in the same period. Meanwhile, the incidence and prevalence of BXW in the endemic areas reduced to below 10% and about 40%, respectively, from over 50% between 2006 and 2010. The high prevalence of BXW indicates that BXW is widely spread but the low incidence shows that BXW is at initial linear phases of disease epidemic across all zones. There are also a few clusters of infection with infected fields at various phases of the disease progress curve. This suggests that it is no longer feasible to classify Uganda’s banana growing areas in different epidemic zones. Consequently the strategies to control BXW across the zone are similar.